A Lotus japonicus mutant defective in nitrate uptake is also affected in the nitrate response to nodulation. (26th March 2014) - Pal'ove‐Balang, P.; García‐Calderón, M.; Pérez‐Delgado, C. M.; Pavlovkin, J.; Betti, M.; Márquez, A. J.; Flemetakis, E.
Abstract A chlorate‐resistant mutant (Ljclo1) of the model legume Lotus japonicus was identified that showed normal levels of nitrate reductase enzyme activity but had decreased uptake of nitrate, as determined from nitrate depletion and electrophysiological measurements. The data suggest that the mutant could be affected specifically in the low‐affinity but not in the high‐affinity nitrate transport system, and also showed decreased uptake of chlorate. Back‐crosses of the mutant plant to the wild type indicated that it is affected in a single Mendelian recessive trait. Thus, the mutation produced in Ljclo1 may be related to some of the low‐affinity nitrate transporters or to a regulatory mechanism associated with nitrate/chlorate uptake. Both size and chlorophyll content in young leaves of the mutant plants were significantly reduced compared to the wild type. In addition, nodulation performance of the mutant plants was similar to the wild type in the absence of any exogenous nitrate. However, the nodule:root biomass ratio in mutant plants was considerably reduced in the presence of 1–2 mm nitrate. The levels of several transcripts for nitrate transport and assimilation genes were determined for the wild type and mutant plants and were slightly different. The results suggest interdependence between nitrate uptake, plant growth and nodulation in Ljclo1 mutant plants.